Evaluating CEFR B1 Alignment of Reading Passages and Comprehension Tasks in EFL Vocational High School Textbook - Danti Roro Anggraini; Novia Trisanti (Universitas Cokroaminoto Palopo, 2026)
This study evaluates the alignment of reading passages and comprehension tasks in the SPLASH English textbook for Grade 10 vocational high school students, claimed to target CEFR B1 level under Indonesia's Merdeka Curriculum, with CEFR B1 descriptors and national learning outcomes. Employing a qualitative descriptive content analysis, all 83 reading passages across units were systematically assessed using a CEFR based checklist covering text type relevance, vocabulary range, sentence complexity, comprehensibility, organization, inferencing potential, and cognitive demands of questions. Findings reveal high overall alignment, with unit scores ranging 92.85 to 96.42 percent (Highly Aligned), strong performance in vocabulary (92.73 percent Fully Supported), main ideas comprehensibility (81.82 percent), and question demands (87.27 percent), though sentence complexity (21.82 percent Minimally Supported) and text organization (18.18 percent) show minor inconsistencies. Dominant categories include Identifying Cues and Inferring (36.14 percent) and Reading for Orientation (34.94 percent), supporting B1 independent reading skills but lacking correspondence genres. The materials substantially align with Merdeka Phase E outcomes for information seeking and inferential skills, yet require broader text variety for full curriculum consistency. These results affirm the textbook's B1 suitability, contrasting prior misalignment studies, and recommend enhanced discourse features and genre diversity for optimal vocational EFL instruction.